Kesehatan Mental Penggemar dalam Lagu My Treasure - Mulyadi, Iffa Salsabila; Soedarsono, Dewi K (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
Music is a powerful communication tool in health communication that can affect the physical, mental and emotional aspects of individuals. Music is also used as a means to deliver health messages. Music has various genres that continue to grow ranging from Pop, Hip Hop, RB, Reggae, Jazz, and others. These music genres then develop into sub-genres of music, one of which is K-Pop or Korean Pop. Indonesia is the third most streamed country in K-Pop music. According to a report from Twitter, Indonesia is the country with the most K-Pop fans in the world. The K-Pop phenomenon in Indonesia is very rampant, especially among young people, especially generation Z. One of the boy groups from South Korea that is currently actively working is Treasure. Treasure specifically released several songs that contain support for fans, one of which is the song "My Treasure". This research uses Stuart Hall's Reception Analysis which discusses how audiences receive messages or interpret and digest messages, as well as semiotic analysis by Ferdinand De Saussure to examine the meaning of the messages conveyed in the song My Treasure. The meaning of the song "My Treasure" can be understood as a message about self-worth, happiness, and hope. Through the reception analysis, it was found that the majority of informants were in the dominant hegemony position, while the rest were in the negotiation position.